Civil Servants' Response In Distributing Professional Zakat Through Baznas - Rimpi azhari; Rizal Fahlefi (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
his study aims to analyze the responses of Civil Servants (PNS/ASN) toward the distribution of professional zakat through the National Zakat Agency (BAZNAS), identify the factors influencing their participation, and explore strategies for optimizing zakat collection within government institutions. The study is motivated by the increasing implementation of professional zakat deductions through payroll systems, which have generated diverse responses among civil servants. While the policy has improved the effectiveness of zakat management, challenges remain, including limited zakat literacy, varying levels of trust in zakat management institutions, and different perceptions regarding the proper distribution of professional zakat. This research employs a qualitative descriptive approach using library research methods. Data were collected from books, scientific journals, government regulations, and official documents related to professional zakat and BAZNAS management. The data were analyzed through descriptive-analytical techniques involving data reduction, classification, presentation, and conclusion drawing. The findings reveal that civil servants generally show positive responses toward the payment of professional zakat through BAZNAS. Participation is influenced by several factors, including religiosity, transparency and accountability of BAZNAS, zakat literacy and socialization programs, government regulatory support, and the convenience of payroll-based payment systems. Transparency in zakat fund management plays a crucial role in building trust among civil servants. Furthermore, continuous socialization efforts enhance awareness and understanding of professional zakat as an Islamic socio-economic instrument. The study also identifies several challenges, such as limited understanding of professional zakat, preferences for direct distribution to beneficiaries, and trust issues in certain regions. Strengthening regulations, improving institutional governance, expanding productive zakat programs, and utilizing digital technology are essential to optimize zakat collection and support poverty alleviation in Indonesia.